Asymptomatic elevation of serum aminotransferase activity: stages of diagnostic search - Yu. A. Tereshchenko; S. Yu. Tereshchenko (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To present algorithm of stepwise clinical and laboratoric testing of patients with long-term asymptomatic elevation of serum aminotransferase activity.Key points. According to epidemiologic data, 10–20% of adult population of the developed countries has increased activity of aminotransferases. The majority of such patients present either no health-related complaints at all, or nonspecific symptoms. Data of common clinical examination and routine laboratory and instrumental tests frequently do not allow to determine satisfactory diagnostic hypothesis. The situation is even more complicated by the absence of domestic practical guidelines on management of these patients. Article presents the algorithm of clinical, laboratory and instrumental testing in described clinical situation. The algorithm is based on the analysis of consensus documents, original studies, experts opinions and authors’ experience.Conclusion. Differential diagnostics at long-term asymptomatic elevation of serum aminotransferase activity should be carried out by step-wise algorithm at which diagnostic search is directed from the most common to more rare possible nosological units.